Streghtening the Quality of Counseling Center in Pesantren through Implementing WOCA (Wisdom Oriented Counseling Approach) Model - Khilman Rofi Azmi; Rifqi Minchatul Ulya (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
The role of Counseling Center in Pesantren takes the important aspect of Santri’s Mental Hygiene. However, related to gender, the dynamics of students have not been well discussed so that it raises other problems related to systemic matters in the private, social, learning and career fields. This article aims to provide an overview of the breakthrough approach that suits the needs of santri, namely WOCA (Wisdom Oriented Counseling Approach) with stages (1) rapport; (2) problem exploration; (3) formulation of the problem; (4) the development of alternative problems; (5) decision making; (6) termination. This study uses a qualitative approach to the type of phenomenology through in depth interviews, observation, and documentation at the Mamba’ul Hikam Islamic Boarding School and Nurul Qur’an Islamic Boarding School in Malang, East Java. The results showed similar patterns used in providing Policy-based “Konseling Berbasis Kebijaksanaan” or (WOCA). The WOCA approach has the main objective of facilitating the counselee to be able to anticipate and solve problems related to self-acceptance and the environment and to develop the counselee's potential optimally. The results of the study prove that through counseling with the WOCA approach, counselors can use to overcome and anticipate problems related to personal, social, learning and career fields. This is because through WOCA counselors can optimize intrapersonal and interpersonal skills within the framework of wisdom values. TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack// This page is in Indonesian Translate to English AfrikaansAlbanianAmharicArabicArmenianAzerbaijaniBengaliBulgarianCatalanCroatianCzechDanishDutchEnglishEstonianFinnishFrenchGermanGreekGujaratiHaitian CreoleHebrewHindiHungarianIcelandicIndonesianItalianJapaneseKannadaKazakhKhmerKoreanKurdish (Kurmanji)LaoLatvianLithuanianMalagasyMalayMalayalamMalteseMaoriMarathiMyanmar (Burmese)NepaliNorwegianPashtoPersianPolishPortuguesePunjabiRomanianRussianSamoanSimplified ChineseSlovakSlovenianSpanishSwedishTamilTeluguThaiTraditional ChineseTurkishUkrainianUrduVietnameseWelsh Always translate Indonesian to EnglishPRO Never translate Indonesian Never translate ejournal.uin-suska.ac.id